Story comprehension, recall and generation in the hearing impaired - P.G, Rashmi (Journal of All India Institute of Speech and Hearing)
The current study was carried out to compare the story comprehension, recall and generation abilities of hearing impaired and their normal peers. Two groups of 15 subjects each were selected within the age range of 8-11 years which was further divided into three groups of one year interval. The study used three tasks that of story comprehension, recall and generation. Single sessions were used with every child. Not more than 30 minutes were taken up by any child. Their responses were transcribed verbatim as well as audio recorded as far as possible.